Expressive Illocutionary Speech Acts Used in Queen Charlotte: A Bridgerton Story Series - Amani, Adibah Saesa; Setiarini, Ni Luh Putu (JEdu: Journal of English Education, 2023)
This research discusses expressive speech acts identified in the Queen Charlotte: A Bridgerton Story series. The objective of this research are to find out the types of expressive speech acts and the most dominant types of expressive speech acts used in the Queen Charlotte: A Bridgerton Story series. The method used in this research was descriptive-qualitative. This research used theory from Searle and Vanderken (1985) to analyze the data. The data in this study were obtained from the utterances used by the character in Queen Charlotte: A Bridgerton Story. The results of this research showed that there are 109 data points found, namely 12 data of apology, 14 data of thanks, three data of condole, two data of condolences, 10 data of complaint, 12 data of lament, 15 data of protest, five data of deplore, six data of boast, 13 data of compliment, six data of praise, and 11 data of welcome (greet). With these data, the expressive speech act of protest is the most types of expressive speech act used in the Queen Charlotte: A Bridgerton Story series.